Test-sequence generation for distributed systems specified in Petri-nets (with application to LOTOS). - Wu, Youwen. (University of Ottawa (Canada), 1990)
This thesis proposes a new approach for the generation of test-sequences for indeterministic distributed systems. The system is specified in a Petri-net extended with internal and special labels so as to include the representation of indeterministic and unusual behaviours. Based on this extended model, a metric called 'degree of indeterminism' is developed for estimating the number of times a test sequence should be executed before a verdict can be made. A fairness model of conformance testing is then presented on the basis of this metric. Also, an iterative algorithm called IPNTEST is developed for generating test sequences and their degrees of indeterminism. The k$\sp{\rm th}$ iteration of IPNTEST generates groups of test sequences which all have the same length k. Test sequences belonging to a group have the same preamble, while different groups may have different preambles. Together, the test groups cover all the bounded feasible paths of the system under test. IPNTEST has been applied to generate test sequences for LOTOS specifications. Based on IPNTEST, an automatic test case generator call LOTOS-TCG has been implemented in the Sun Workstation.
Keywords: Engineering, Electronics and Electrical.